Research Status and Progress of Transcritical CO2 Heat Pump Drying Systems - Liu Shengchun; Lin Jiansen; Hua Xue; Li Xiongya; Dai Baomin; Sun Zhili; Shao Changbo (Zhileng xuebao)
The drying process consumes large amounts of energy in industrial and agricultural production. Research and practical applications show that compared with other drying technologies, the heat pump drying technology has better energy-saving potential and economic benefits. As a natural working medium, CO2 is environmentally friendly. The transcritical CO2 cycle has a clear temperature glide, which is more suitable for heat pump drying than the subcritical cycle with a constant condensing temperature of a conventional working fluids. In this paper, the research status of the transcritical CO2 heat pump drying systems is described. The feasibility of the application, system model establishment and key parameter analysis, experimental research, and system optimization of CO2 heat pump drying system are discussed in depth. The advantages and disadvantages of various CO2 heat pump drying system optimization methods are summarized. Existing limitations in the current research of transcritical CO2 heat pump drying systems are proposed, thereby providing a reference for future research applications of CO2 heat-pump-drying technology.